A focus group study on the potential of autonomous vehicles as a viable transportation option: Perspectives from people with disabilities and public transit agencies. (April 2020) - Hwang, Jinuk; Li, Wei; Stough, Laura; Lee, Chanam; Turnbull, Katherine
Highlights: This study explores how people with disabilities and public transit agencies perceive autonomous vehicle transportation (AVT). Focus groups were used to determine perceptions of AVT. Expectations, concerns, and needs of people with disabilities regarding AVT were identified. Mobility issues of people with disabilities increased the expectations for AVT. More targeted AVT strategies to improve mobility of people with disabilities were discussed. Abstract: Autonomous vehicle (AV) technology is becoming one of the most promising alternatives to improve mobility for people with disabilities. Nevertheless, how people with disabilities perceive AV as transportation services has not been explored. Also, limited information exists about how public transit agencies comprehend and perceive autonomous vehicle transportation (AVT) services. This study discusses mobility issues for people with disabilities and explores the potential of AVT to serve that population, particularly those with visual impairments or physical disabilities. Researchers conducted six focus groups comprising people with disabilities (N = 23) and public transit service experts (N = 10) in Austin, Texas and Houston, Texas. Each session was audio-recorded and analyzed using conventional content analysis. This study identified people with disabilities' mobility issues related to: (1) current transit services (including fixed-route and paratransit services) and (2) the quality of neighborhood built environments. Both people with disabilities and transit experts expected that AVT could mitigate current mobility issues, especially in improved built environments. However, participants with disabilities also expressed concerns and anxieties regarding AVT. Transit experts agreed that more targeted strategies would be needed to overcome possible barriers to AVT for people with disabilities. This study provides insights on shaping AVT strategies and policies relevant to improving mobility for people with disabilities.